The sealing ability of MTA apical plugs exposed to a phosphate-buffered saline - Josiane de Almeida; Ana Maria Hecke Alves; Roberto Ferreira de Melo; Mara Cristina Santos Felippe; Eduardo Antunes Bortoluzzi; Cleonice da Silveira Teixeira; Wilson Tadeu Felippe (University of São Paulo, 2013)
OBJECTIVE: The aim of this study was to evaluate the influence of exposure of the mineral trioxide aggregate (MTA) - with and without calcium chloride (CaCl2) - to phosphate-buffered saline (PBS) on the apical microleakage using a glucose leakage system. MATERIAL AND METHODS: Sixty root segments were randomly divided into 4 experimental groups (n=15). After resecting the apical segments and enlarging the canals with Gates-Glidden drills, the apical cavities were filled with MTA with or without CaCl2 and the root canals were dressed with a moistened cotton pellet or PBS, as follows: 1) MTA/cotton pellet; 2) MTA/PBS; 3) MTA+10%CaCl2/cotton pellet; 4) MTA+10%CaCl2/PBS. All root segments were introduced in floral foams moistened with PBS. After 2 months, all root segments were prepared to evaluate the glucose leakage along the apical plugs. The amount of glucose leakage was measured following an enzymatic reaction and quantified by a spectrophotometer. Four roots were used as controls. The data were analyzed using Kruskal-Wallis and Mann-Whitney tests (p<0.05). RESULTS: There were no differences between groups 1 and 2 (p>0.05), and 3 and 4 (p>0.05). The addition of CaCl2 to the MTA significantly decreased its sealing ability (p<0.05). CONCLUSION: The interaction with PBS did not improve the MTA sealing ability. The addition of CaCl2 to the MTA negatively influenced the apical seal.